How public theologies can better address fascism, nationalism, and our impatience with God's reign. Issue 1 (4th March 2019) - Larson, Duane
Abstract: This article considers the problems of fascism and nationalism today, particularly in the United States, and summarizes definitions of public theology that would be adequate to the current situation. Then three non‐theologians are consulted as resources for public theology: diplomat Madeleine Albright, philosopher Martha Nussbaum, and journalist Chris Hedges. I close with synthetic conclusions, including comment on the necessity of prayer, about the desired character of public theologies today.